Inconstitucionalidad del juzgamiento de contravenciones en la Ley Orgánica de Transporte Terrestre, Tránsito y Seguridad Vial en el Ecuador - Yucta Montero, Renato Alberto (2016)
The present work was developed in a text that allows interpreted the reality in the judicial system when judging traffic infringements and the parties cannot access a second instance when there a disagreement in the judgment. For the effect we proposed as actions: a) Sustain the theoretical and conceptual contents that allows created a Draft reform Law at 178 Article of the Organic Law of Land Transport, Traffic and Road Safety, that establish an appeal resource in the violations sentences, as a recognizance of a due process and the Constitution, international treaties and conventions. b) Within the work was performing a descriptive research, using scientific methodology, theoretical methods such as inductive, deductive, analytical and synthetic methods, in the empirical methods was applied the observation and inquest applied to the Users of Traffic Courts and law professionals in the province. c) The topic have favorable results, the 99.05% of respondents support the proposal for the creation of a Draft reformatory law in 178 Article of the Organic Law of Land Transport, Traffic and Road Safety; so be accessible to all agencies within the judicial system. This research was developed from a conceptual framework that includes the concepts and definitions of what constitutes Law of Land Transport, Traffic and Road Safety, their special characteristics, their rights and guarantees, the stages of prosecution. A doctrinal framework that involves analyzing the criteria of writers and scholars of the problem; fundamental characteristics. The legal framework in analyzing the Constitution of the Republic of Ecuador concerning with the contraventions. We finally found the field research that includes the analysis of the results of surveys and interviews, analysis and interpretation, a chapter devoted to the discussion that involves the study and analysis, and verification of hypothesis testing objectives, the legal basis for legal reform proposal, the conclusions and recommendations and bequeaths Reform Project